High-dispersion nickel-based carbon-nitrogen catalyst as well as preparation method and application thereof

Through the synergistic pyrolysis method of NiAl-LDH and 1,10-o-phenanthroline and carbon black, a high dispersion nickel-based carbon-nitrogen catalyst was prepared, which solved the problems of complex preparation and unstable performance of nickel-based electrocatalysts, and achieved high-efficiency electrocatalytic CO2 reduction, with excellent catalytic activity and stability, and was suitable for industrial applications.

CN120400890AActive Publication Date: 2025-08-01BEIJING UNIV OF CHEM TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510909451.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-02
Publication Date
2025-08-01
Estimated Expiration
2045-07-02

AI Technical Summary

Technical Problem

In the CO2 reduction reaction, existing nickel-based electrocatalysts have problems such as complex preparation process, low utilization rate of activity centers, and unstable catalytic performance.

Method used

A high-dispersed nickel-based carbon-nitrogen catalyst was prepared by heat treatment of NiAl-LDH precursor and 1,10-o-phenanthroline and carbon black under a nitrogen atmosphere by dispersing and mixing uniformly, and a single-step pyrolysis was performed. The decomposition characteristics of NiAl-LDH and the nitrogen source of 1,10-o-phenanthroline were used to form uniformly distributed nickel active sites in the carbon framework to inhibit metal agglomeration and improve catalytic performance.

Benefits of technology

It has achieved simple preparation of a highly dispersed nickel-based carbon-nitrogen catalyst, uniform distribution of nickel active sites, excellent electrocatalytic activity and selectivity, and the CO selectivity Faraday efficiency is greater than 90%, which has good stability and is suitable for large-scale production and industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120400890A_ABST
    Figure CN120400890A_ABST
Patent Text Reader

Abstract

The invention relates to a high-dispersion nickel-based carbon-nitrogen catalyst as well as a preparation method and application thereof. The preparation method comprises the following steps: 1, synthesizing a hydrotalcite precursor; step 2, preparing a roasting precursor; and 3, preparing the high-dispersion nickel-based carbon-nitrogen catalyst. The preparation method of the high-dispersion nickel-based carbon-nitrogen catalyst is simple and convenient, raw materials are cheap, and the catalyst is suitable for large-scale production. The nickel in the high-dispersion nickel-based carbon-nitrogen catalyst is highly dispersed, and the electrocatalytic activity and selectivity are excellent; the carbon-nitrogen carrier has the effects of stabilizing the structure, regulating and controlling electrons and the like, and electron transfer and intermediate adsorption are facilitated. The high-dispersion nickel-based carbon-nitrogen catalyst has high catalytic activity and high stability, the Faraday efficiency of CO is not obviously attenuated after continuous electrolysis for 30 hours, and the high-dispersion nickel-based carbon-nitrogen catalyst has good stability and industrial application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of electrocatalysis, and particularly relates to a highly dispersed nickel-based carbonitride catalyst, a preparation method thereof, and an application thereof. Background Art

[0002] With the increasingly severe global climate change, carbon dioxide emissions have become one of the key factors affecting environmental sustainable development. Converting carbon dioxide (CO2RR) into valuable carbon-based chemicals such as carbon monoxide, formic acid, and methanol through electrocatalytic reduction not only helps to achieve carbon recycling but also provides a new path for the efficient storage and utilization of renewable energy. Currently, noble metal (such as Au, Ag)-based electrocatalysts exhibit good activity and selectivity in CO2RR, but their high cost limits large-scale applications. In contrast, nickel-based catalysts have become one of the representatives of non-noble metal electrocatalysts due to their abundant reserves, good CO2 adsorption activity, and low preparation cost. However, traditional nano-nickel catalysts face problems such as agglomeration and low utilization rate of metal active sites, which limit their further application in CO2RR.

[0003] In recent years, single-atom catalysts (SACs) have shown excellent performance in heterogeneous catalytic reactions such as CO2RR due to their maximum atomic utilization rate and unique electronic structure regulation ability. However, the preparation methods of existing highly dispersed nickel-based catalysts usually have problems such as complex precursor design, difficult ligand synthesis, template assistance required, or multi-step heat treatment at high cost, which are not conducive to large-scale synthesis and industrial applications. Patent document CN118925768A synthesizes nitrogen-doped porous carbon using the high internal phase emulsion template method, and then highly dispersed nickel-based is loaded on the nitrogen-doped porous carbon by the impregnation method. After high-temperature calcination, a highly dispersed nickel-based catalyst is obtained. Patent document CN118910651A prepares a PVP@ZIF-8 composite material by the room-temperature stirring method using methanol as a solvent, and uses this MOF material as a precursor for high-temperature carbonization and pyrolysis. The product is subjected to operations such as pickling and drying to obtain a porous nitrogen-doped carbon material, and then nickel-based single-atom catalysts are obtained through impregnation pyrolysis. The methods for synthesizing highly dispersed nickel-based catalysts in the above two patents require template assistance or multi-step treatment, which are not conducive to large-scale synthesis and industrial applications.

[0004] To address the above issues, researchers have gradually focused on using inexpensive metal sources such as layered double hydroxides (LDHs), as well as ligands with simple structures and conductive carbon carriers to construct highly dispersed catalysts. Although there have been attempts in the literature to use NiAl-LDH as a precursor for pyrolysis to prepare Ni-based catalytic materials, patent document CN115074750A synthesizes hydrotalcite by hydrothermal method and then co-pyrolyzes the hydrotalcite and nitrogen source to prepare a highly dispersed nickel-based / AlN co-embedded carbon nanotube electrocatalyst. However, the operation of preparing hydrotalcite by hydrothermal method is relatively complex and not conducive to subsequent industrialization. Therefore, how to regulate the dispersion state of Ni, how to simply prepare catalytic materials and endow them with the ability of highly selective electroreduction of CO2 still remains challenging.

[0005] Therefore, there is an urgent need to develop a catalyst preparation method with simple process, inexpensive raw materials, adjustable highly dispersed structure and suitable for efficient electrocatalytic CO2 reduction, so as to promote the industrial transformation and application of this technology, which is of great significance in the fields of catalysis, energy, etc. Summary of the Invention

[0006] The technical problems solved by the present invention: the problems existing in the preparation process of existing nickel-based electrocatalysts in the CO2 reduction reaction, such as complex preparation process, low utilization rate of active centers, unstable catalytic performance, etc.

[0007] In view of the technical problems existing in the prior art, the present invention designs a highly dispersed nickel-based carbon nitride catalyst, a preparation method thereof and an application thereof.

[0008] It should be noted that in the present invention, unless otherwise specified, the specific meaning of "including" involving composition limitations and descriptions includes both open "including", "containing" and their similar meanings, as well as closed "consisting of..." and their similar meanings.

[0009] To solve the above-mentioned existing technical problems, the present invention adopts the following solutions: A preparation method of a highly dispersed nickel-based carbon nitride catalyst, comprising the following steps: Step 1: Synthesize a hydrotalcite precursor; Weigh nickel nitrate hexahydrate and aluminum nitrate nonahydrate and dissolve them in deionized water, denoted as solution A, and prepare sodium hydroxide solution B. Use a colloid mill to synthesize a hydrotalcite precursor, namely NiAl-LDH precursor; Step 2: Prepare a calcination precursor; Disperse the NiAl-LDH precursor, 1,10-phenanthroline and carbon black in an ethanol solution, disperse evenly, dry in vacuum and then grind and crush to obtain a calcination precursor; Step 3: Prepare a highly dispersed nickel-based carbon nitride catalyst; The calcined precursor obtained in step 2 is heat-treated under a nitrogen atmosphere to obtain a highly dispersed nickel-based carbon-nitrogen catalyst, namely, a Ni-NC catalyst; In step 1, the molar ratio of nickel nitrate hexahydrate to aluminum nitrate nonahydrate in solution A is 2:1-4:1; The total concentration of the nitrate solution A is 0.05-1.0 mol / L; The concentration of the sodium hydroxide solution B is 1 mol / L-4 mol / L; In step 2, the mass ratio of NiAl-LDH precursor to (1,10-phenanthroline + carbon black) is 0.01 to 0.5. The mass percentage of carbon black in the mixture of 1,10-phenanthroline and carbon black is 10-90%.

[0010] Furthermore, the synthesis of the hydrotalcite precursor by colloid milling is specifically as follows: while the colloid mill is rotating at a speed of 1500-9000 rpm, salt solution A and sodium hydroxide solution B are poured into the colloid mill at the same speed for 1-120 minutes, the mixture is taken out, washed to neutrality, dried by rotary evaporation at 40-80°C, and ground into powder.

[0011] Furthermore, in step 3, the heat treatment temperature is 550°C-950°C, the heating rate is 0.5-10°C / min, the nitrogen flow rate is 20-200 mL / min, and the heat treatment time is 1-5 h.

[0012] The invention also discloses a highly dispersed nickel-based carbon-nitrogen catalyst, which is prepared according to the above preparation method.

[0013] Furthermore, the highly dispersed nickel-based carbon-nitrogen catalyst has the following characteristics: (1) Using carbon and nitrogen as carriers, nickel active sites are evenly distributed on the surface; (2) Contains three types of doped nitrogen: graphitic N, pyridinic N, and pyrrolic N; (3) Nickel exists in the form of Ni-Ni.

[0014] Furthermore, the mass fraction of Ni in the highly dispersed nickel-based carbon-nitrogen catalyst is 0.5-5wt%, and Ni is dispersed in the form of extremely small clusters.

[0015] Furthermore, the total mass fraction of nitrogen doping in the highly dispersed nickel-based carbon-nitrogen catalyst is 1-15wt%, of which graphite N accounts for 0-40%, pyridine N accounts for 20-80%, and pyrrole N accounts for 10-40%.

[0016] The present invention also discloses an application of the highly dispersed nickel-based carbon-nitrogen catalyst in an electrocatalytic reaction for selectively reducing CO2 to carbon monoxide.

[0017] In the application of the present invention, a working electrode needs to be prepared; In an H-type electrolytic cell separated by a Nafion 117 proton exchange membrane (PEM) into an anode chamber and a cathode chamber, a platinum sheet serves as the counter electrode, and Ag / AgCl (3.5 M saturated KCl solution) serves as the reference electrode. The catalyst loading is 1 mg / cm 2 of hydrophobic carbon paper is used as the working electrode. 20 mL of 0.5 M KHCO3 solution is filled into the electrolytic cell. Before testing, CO2 is bubbled into the electrolyte at a rate of 20 mL / min for 30 min until saturation, and then CO2 is electrochemically reduced at a constant potential under continuous CO2 bubbling. The Faradaic efficiency of the CO2 reduction products at different potentials is calculated.

[0018] During the constant potential reduction process, the potential is controlled at -1.4 V - -1.8 V. When preparing the working electrode, 5 mg of the catalyst is dispersed in 1 mL of ethanol solution, and 20 μL of Nafion membrane solution is added. After ultrasonic treatment for 30 min, a uniform ink is formed. 200 μL is taken out and evenly dropped on 1 cm 2 carbon paper and used after drying under an infrared lamp.

[0019] The highly dispersed nickel-based carbonitride catalyst of the present invention is applied to the aqueous CO2 electroreduction reaction, and the CO selectivity (Faradaic efficiency) is greater than 90% in the potential window of -1.4 V to -1.8 V (vs. Ag / AgCl).

[0020] In the present invention, the uniform dispersion in step 2 is achieved by ultrasonic treatment for 20 - 40 min. Generally, no special requirements are made for the ultrasonic power, based on the effect of achieving uniform dispersion.

[0021] In the present invention, the vacuum drying in step 2 is generally completed in a vacuum drying oven at 60 - 80 °C.

[0022] In the Ni-N-C catalyst prepared in the present invention, nickel active sites are uniformly distributed in the carbonitride matrix.

[0023] In the present invention, 1,10-phenanthroline acts as a nitrogen source and participates in the construction of the carbon skeleton during the pyrolysis process, forming a carbonitride skeleton rich in nitrogen functional groups; carbon black provides a high specific surface area and an excellent conductive network, effectively promoting electron transport; nickel released during the pyrolysis of NiAl-LDH is nano-confined and anchored in the carbonitride structure, significantly inhibiting metal agglomeration and obtaining highly dispersed nickel active sites, thereby improving the catalytic performance and structural stability.

[0024] In the present invention, a synergistic combination of nickel-containing layered double hydroxide (NiAl-LDH), high specific surface area carbon black and nitrogen source 1,10-phenanthroline is used in the catalyst preparation process. After pre-uniform dispersion and single-step pyrolysis, it is significantly superior to the existing multi-step impregnation-roasting or simple physical mixing methods. The essence of this technology is to utilize the staged decomposition characteristics of NiAl-LDH during high-temperature cracking, so that nickel is gradually precipitated in the carbon skeleton at a relatively slow rate. The interlayer "nano-confinement" effect can inhibit Ni from precipitating in the early and middle stages of pyrolysis. 2+ The rapid migration and disordered agglomeration cause it to preferentially deposit on the carbon black surface or defective areas. At the same time, the intermediate carbon and nitrogen fragments generated in the initial pyrolysis of 1,10-phenanthroline can react with the released Ni 2+ The formation of transient coordination complexes guides Ni to enrich in nitrogen sites at the molecular scale, reducing the risk of forming large metal agglomerates under high temperature conditions. In the late pyrolysis stage, these nitrogen sources evolve into various active nitrogen sites such as graphitic N, pyridinic N, and pyrrolic N during the carbonization and graphitization process, and gradually reduce to Ni 0 The nickel clusters form Ni at the interface of the support x –N x -C cooperative structure or nickel-rich electron interface, further regulates d orbital electron filling, and improves the adsorption and activation efficiency of CO2 molecules on the catalyst surface. Carbon black not only provides a porous conductive network, significantly improving the electron migration rate, but also can capture some Ni species due to its rich surface defects and dislocations, thereby strengthening the metal-carbon coupling interface. Through such a strategy of pre-molecular-level uniform mixing and simultaneous realization of metal confinement, nitrogen cooperative doping and directional regulation of carbon skeleton structure in a single-step pyrolysis, the present invention successfully solves the problems of metal agglomeration, uneven nitrogen doping, and chaotic interface charge distribution that are easily caused by the traditional method of first loading and then carbonization, so that nickel species are embedded in the carbon-nitrogen skeleton with higher dispersion, more reasonable electronic structure and more stable interface morphology, thereby effectively improving the electrocatalytic CO2 reduction performance and long-term stability.

[0025] In the present invention, the metal source in the catalyst preparation method can be other nickel-based hydrotalcites, such as one or more of NiCo-LDH, NiFe-LDH, etc.; The nitrogen source may also be one or more other organic substances or ligands containing nitrogen; The carbon source can also be other carbon-containing inorganic substances besides carbon black, such as carbon nanotubes, C 60 One or more of the above.

[0026] In the present invention, there is no need to soak the product with dilute acid (such as 0.1M HCl) (to remove possible residual metal particles), which also highlights the simplicity of the catalyst preparation method of the present invention.

[0027] The present invention provides a highly dispersed nickel-based carbonitride catalyst, a preparation method thereof, and an application thereof, which have the following beneficial effects: 1. The preparation method of the highly dispersed nickel-based carbonitride catalyst of the present invention is simple, the raw materials are inexpensive, and it is suitable for large-scale production.

[0028] 2. The nickel in the highly dispersed nickel-based carbonitride catalyst of the present invention is highly dispersed, and it has excellent electrocatalytic activity and selectivity (FE CO -97%), that is, the Faraday efficiency of carbon monoxide is about 97%; the carbonitride support has functions such as a stable structure and electron regulation, which is conducive to electron transfer and intermediate adsorption.

[0029] 3. The highly dispersed nickel-based carbonitride catalyst in the present invention has high catalytic activity and high stability at the same time. After continuous electrolysis for 30 h, the Faraday efficiency of CO has no obvious attenuation, and it has good stability and industrial application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 : It is a preparation flow chart of the highly dispersed nickel-based carbonitride catalyst of the present invention; Figure 2 : It is a scanning electron microscope (SEM) and transmission electron microscope (TEM) image of the highly dispersed nickel-based carbonitride catalyst prepared in Example 1 of the present invention; Figure 3 : It is an X-ray diffraction spectrum (XRD) and X-ray photoelectron spectrum (XPS) diagram of the highly dispersed nickel-based carbonitride catalyst prepared in Examples 1-3 of the present invention, including an N 1s high-resolution diagram showing the N type distribution; Figure 4 : It is a Ni K-edge EXAFS spectrum and Fourier transform spectrum diagram of the highly dispersed nickel-based carbonitride catalyst prepared in Example 1 of the present invention; Figure 5 : It is a Faraday efficiency (FE) curve of the CO2 electroreduction reaction of different materials in Examples 1-3 and Comparative Examples 1-5 at different potentials and a current (LSV) curve of Examples 1-3; Figure 6 : It is a stability test curve of the highly dispersed nickel-based carbonitride catalyst prepared in Example 1 of the present invention. DETAILED DESCRIPTION OF THE INVENTION

[0031] The following further describes the present invention in conjunction with specific examples and the accompanying drawings: Example 1 Preparation of Ni-N-C-750

[0032] Ni-N-C-750 is a highly dispersed nickel-based doped carbonitride catalytic material prepared by co-thermal decomposition treatment of nickel-aluminum hydrotalcite, 1,10-phenanthroline (phen), and carbon black at 750 °C.

[0033] Weigh nickel nitrate hexahydrate (13.96 g) and aluminum nitrate nonahydrate (3.34 g) and dissolve them in 80 mL of deionized water, denoted as solution A. Also, weigh sodium hydroxide (8.96 g) and dissolve it in 80 mL of deionized water, denoted as solution B. Use a colloid mill to synthesize the hydrotalcite precursor, namely the NiAl-LDH precursor; Among them, the total concentration of the nitrate solution A at this moment is 0.8 mol / L; the concentration of the sodium hydroxide solution B is 2 mol / L; The specific process of synthesizing the hydrotalcite precursor with a colloid mill is as follows: At a colloid mill rotation speed of 6000 rpm, simultaneously pour solution A and sodium hydroxide solution B. After pouring, maintain at this rotation speed for 60 min, take out, wash until neutral, rotary evaporate and dry at 60 °C, and grind and crush.

[0034] Take 6 mg of NiAl-LDH powder (Ni:Al molar ratio is 3:1), 100 mg of 1,10-phenanthroline (phen), 100 mg of carbon black (Vulcan XC-72). The mass ratio of NiAl-LDH precursor / (1,10-phenanthroline + carbon black) is 0.03. Among the mixture of 1,10-phenanthroline and carbon black, the mass percentage of carbon black is 50%. Add the above three components into an appropriate amount of absolute ethanol, and ultrasonically disperse for 30 minutes to obtain a uniformly mixed slurry.

[0035] Dry the slurry (60 °C, in a vacuum drying oven) and then grind it to obtain the precursor mixture.

[0036] Place the precursor mixture in a quartz boat, put it into a tube furnace, heat it to 750 °C in a nitrogen atmosphere (heating rate 5 °C / min), keep it warm for 2 hours, and then naturally cool to room temperature to obtain a black powder, which is the catalyst Ni-N-C-750.

[0037] Prepare a working electrode. Disperse 5 mg of the catalyst in 1 mL of ethanol solution, and add 20 μL of Nafion membrane solution, ultrasonically for 30 min to form a uniform ink. Take out 200 μL and evenly drop it on a 1 cm 2 carbon paper, dry it under an infrared lamp and then use it. In an H-type electrolytic cell separated by a Nafion117 proton exchange membrane (PEM) into an anode chamber and a cathode chamber, a platinum sheet is used as the counter electrode, and Ag / AgCl (3.5 M saturated KCl solution) is used as the reference electrode. The catalyst loading is 1 mg / cm 2The hydrophobic carbon paper serves as the working electrode. 20 mL of 0.5 M KHCO3 solution is loaded into the electrolytic cell. Before testing, CO2 is bubbled into the electrolyte at a rate of 20 mL / min for 30 min until saturation. Then, under the condition of continuously introducing CO2, CO2 is reductively electrolyzed at a constant potential at the cathode, and the Faraday efficiencies of the CO2 reduction products (CO, H2) at different potentials are calculated.

[0038] Example 2: Preparation of Ni-N-C-550

[0039] Ni-N-C-550 is a highly dispersed nickel-based doped carbon nitride catalytic material prepared by co-pyrolysis treatment of nickel-aluminum hydrotalcite, 1,10-phenanthroline (phen), and carbon black at 550 °C.

[0040] Weigh nickel nitrate hexahydrate (0.78 g) and aluminum nitrate nonahydrate (0.28 g) and dissolve them in 80 mL of deionized water, denoted as solution A. Also, weigh sodium hydroxide (4.48 g) and dissolve it in 80 mL of deionized water, denoted as solution B. Use a colloid mill to synthesize the hydrotalcite precursor, namely the NiAl-LDH precursor. Among them, the total concentration of the nitrate solution A at this moment is 0.05 mol / L; the concentration of the sodium hydroxide solution B is 1 mol / L. The specific process of synthesizing the hydrotalcite precursor with a colloid mill is as follows: At a colloid mill rotation speed of 1500 rpm, simultaneously pour in the salt solution A and the sodium hydroxide solution B. After pouring, maintain at this rotation speed for 120 min, take it out, wash it until neutral, dry it by rotary evaporation at 40 °C, and grind it into powder.

[0041] Take 2 mg of NiAl-LDH powder (Ni:Al molar ratio is 2:1), 180 mg of 1,10-phenanthroline (phen), and 20 mg of carbon black (Vulcan XC-72). The mass ratio of NiAl-LDH precursor / (1,10-phenanthroline + carbon black) is 0.01. Among the mixture of 1,10-phenanthroline and carbon black, the mass percentage of carbon black is 10%. Add the above three components to an appropriate amount of absolute ethanol, and after ultrasonic dispersion for 30 minutes, a uniform mixed slurry is obtained.

[0042] Dry the slurry (70 °C, vacuum drying oven) and then grind it to obtain a precursor mixture.

[0043] Place the precursor mixture in a quartz boat, put it into a tubular furnace, heat it to 550 °C (heating rate 0.5 °C / min) under a nitrogen atmosphere, keep it warm for 1 hour, and then naturally cool it to room temperature to obtain a black powder, which is the catalyst Ni-N-C-550.

[0044] Prepare a working electrode by dispersing 5 mg of the catalyst in 1 mL of ethanol solution, adding 20 μL of Nafion membrane solution, and sonicating for 30 min to form a homogeneous ink. Take out 200 μL and evenly drop it on a 1 cm 2 carbon paper, and use it after drying under an infrared lamp. In an H-type electrolytic cell separated by a Nafion 117 proton exchange membrane (PEM) into an anodic cell and a cathodic cell, a platinum sheet is used as the counter electrode, and Ag / AgCl (3.5 M saturated KCl solution) is used as the reference electrode. The hydrophobic carbon paper with a catalyst loading of 1 mg / cm 2 is used as the working electrode. 20 mL of 0.5 M KHCO3 solution is filled in the electrolytic cell. Before testing, bubble CO2 into the electrolyte at 20 mL / min for 30 min until saturated, and then under the condition of continuously bubbling CO2, reduce CO2 at a constant cathodic potential, and calculate the Faraday efficiency of the CO2 reduction products (CO, H2) at different potentials.

[0045] Example 3: Preparation of Ni-N-C-950

[0046] Ni-N-C-950 is a highly dispersed nickel-based doped carbon nitride catalytic material prepared by co-pyrolysis treatment of nickel-aluminum hydrotalcite, 1,10-phenanthroline (phen), and carbon black at 950 °C.

[0047] Weigh nickel nitrate hexahydrate (18.61 g) and aluminum nitrate nonahydrate (3.34 g) and dissolve them in 80 mL of deionized water, denoted as solution A. Also, weigh sodium hydroxide (17.92 g) and dissolve it in 80 mL of deionized water, denoted as solution B. Use a colloid mill to synthesize a hydrotalcite precursor, namely NiAl-LDH precursor; Among them, the total concentration of the nitrate solution A at this moment is 1.0 mol / L; the concentration of the sodium hydroxide solution B is 4 mol / L; The specific method of synthesizing the hydrotalcite precursor with a colloid mill is as follows: at a colloid mill rotation speed of 9000 rpm, pour solution A and sodium hydroxide solution B simultaneously. After pouring, maintain at this rotation speed for 1 min, take out, wash until neutral, spin-dry at 80 °C, and grind into powder.

[0048] Take 100 mg of NiAl-LDH powder (molar ratio of Ni:Al is 4:1), 20 mg of 1,10-phenanthroline (phen), and 180 mg of carbon black (Vulcan XC-72). The mass ratio of NiAl-LDH precursor / (1,10-phenanthroline + carbon black) is 0.5. Among the mixture of 1,10-phenanthroline and carbon black, the mass percentage of carbon black is 90%. Add the above three components to an appropriate amount of absolute ethanol, and after sonicating and dispersing for 30 minutes, a homogeneous mixed slurry is obtained.

[0049] The slurry was dried (at 80 °C in a vacuum drying oven) and then ground to obtain a precursor mixture.

[0050] The precursor mixture was placed in a quartz boat and then put into a tube furnace. It was heated to 950 °C (heating rate: 10 °C / min) in a nitrogen atmosphere, held at this temperature for 5 hours, and then naturally cooled to room temperature to obtain a black powder, which was the catalyst Ni-N-C-950.

[0051] A working electrode was prepared. 5 mg of the catalyst was dispersed in 1 mL of ethanol solution, and 20 μL of Nafion membrane solution was added. After ultrasonic treatment for 30 min, a uniform ink was formed. 200 μL of the ink was taken out and evenly dropped on a 1 cm 2 carbon paper, and it was used after drying under an infrared lamp. In an H-type electrolytic cell separated by a Nafion 117 proton exchange membrane (PEM) into an anode chamber and a cathode chamber, a platinum sheet was used as the counter electrode, and Ag / AgCl (3.5 M saturated KCl solution) was used as the reference electrode. The hydrophobic carbon paper with a catalyst loading of 1 mg / cm 2 was used as the working electrode. 20 mL of 0.5 M KHCO3 solution was filled into the electrolytic cell. Before the test, CO2 was bubbled into the electrolyte at a rate of 20 mL / min for 30 min until saturated. Then, under the condition of continuously introducing CO2, CO2 was electrochemically reduced at a constant potential at the cathode, and the Faraday efficiencies of the CO2 reduction products (CO, H2) at different potentials were calculated.

[0052] Comparative Example 1 Preparation of Ni-N-750

[0053] Ni-N-750 is a highly dispersed nickel-based doped carbon nitride catalytic material prepared by co-pyrolysis treatment of nickel-aluminum hydrotalcite and 1,10-phenanthroline (phen) at 750 °C.

[0054] 13.96 g of nickel nitrate hexahydrate and 3.34 g of aluminum nitrate nonahydrate were weighed and dissolved in 80 mL of deionized water, denoted as solution A. And 8.96 g of sodium hydroxide was weighed and dissolved in 80 mL of deionized water, denoted as solution B. A hydrotalcite precursor, namely NiAl-LDH precursor, was synthesized using a colloid mill. Among them, the total concentration of the nitrate solution A at this moment was 0.8 mol / L; the concentration of the sodium hydroxide solution B was 2 mol / L; The specific process of synthesizing the hydrotalcite precursor using a colloid mill was as follows: At a colloid mill rotation speed of 6000 rpm, solution A and solution B were simultaneously poured in. After pouring, it was maintained at this rotation speed for 60 min, taken out, washed until neutral, dried by rotary evaporation at 60 °C, and ground into powder.

[0055] Take 6 mg of NiAl-LDH powder (Ni:Al molar ratio is 3:1) and 100 mg of 1,10-phenanthroline (phen). Add the above two components into an appropriate amount of absolute ethanol, and after ultrasonic dispersion for 30 minutes, a homogeneous mixed slurry is obtained. Dry the slurry (60 °C, in a vacuum drying oven) and then grind it to obtain a precursor mixture.

[0056] Place the precursor mixture in a quartz boat, put it into a tube furnace, heat it to 750 °C under a nitrogen atmosphere (heating rate 5 °C / min), hold for 2 hours, and then naturally cool to room temperature to obtain a black powder, which is the catalyst Ni-N-750.

[0057] Prepare a working electrode. Disperse 5 mg of the catalyst in 1 mL of ethanol solution, and add 20 μL of Nafion membrane solution, and ultrasonicate for 30 min to form a homogeneous ink. Take out 200 μL and evenly drop it on a 1 cm 2 carbon paper, and use it after drying under an infrared lamp. In an H-type electrolytic cell separated by a Nafion117 proton exchange membrane (PEM) into an anode chamber and a cathode chamber, a platinum sheet is used as the counter electrode, and Ag / AgCl (3.5 M saturated KCl solution) is used as the reference electrode. The hydrophobic carbon paper with a catalyst loading of 1 mg / cm 2 is used as the working electrode. Load 20 mL of 0.5 M KHCO3 solution into the electrolytic cell. Before testing, bubble 20 mL / min of CO2 into the electrolyte for 30 min until saturated, and then under the condition of continuously introducing CO2, reduce CO2 at a constant cathode potential, and calculate the Faraday efficiency of the CO2 reduction products (CO, H2) at different potentials.

[0058] Comparative Example 2 Preparation of Ni-C-750

[0059] Ni-C-750 is a highly dispersed nickel-based doped carbon nitride catalytic material prepared by co-pyrolysis treatment of nickel-aluminum hydrotalcite and carbon black at 750 °C.

[0060] Weigh nickel nitrate hexahydrate (13.96 g) and aluminum nitrate nonahydrate (3.34 g) and dissolve them in 80 mL of deionized water, denoted as solution A, and weigh sodium hydroxide (8.96 g) and dissolve it in 80 mL of deionized water, denoted as solution B. Use a colloid mill to synthesize a hydrotalcite precursor, that is, a NiAl-LDH precursor; Among them, the total concentration of the nitrate solution A at this moment is 0.8 mol / L; the concentration of the sodium hydroxide solution B is 2 mol / L; The synthesis of the hydrotalcite precursor using a colloid mill is as follows: While the colloid mill is rotating at a speed of 6000 rpm, pour salt solution A and sodium hydroxide solution B simultaneously. After pouring, maintain at this speed for 60 minutes, then take out, wash until neutral, dry by rotary evaporation at 60 °C, and grind into powder.

[0061] Take 6 mg of NiAl-LDH powder (Ni:Al molar ratio is 3:1) and 100 mg of carbon black (Vulcan XC-72). Add the above two components to an appropriate amount of absolute ethanol, and after ultrasonic dispersion for 30 minutes, a uniformly mixed slurry is obtained. After drying the slurry (60 - 80 °C, vacuum drying oven) and then grinding, a precursor mixture is prepared.

[0062] Place the precursor mixture in a quartz boat, put it into a tube furnace, heat it to 750 °C in a nitrogen atmosphere (heating rate 5 °C / min), hold for 2 hours, and then naturally cool to room temperature to obtain a black powder, which is the catalyst Ni-C-750.

[0063] Prepare a working electrode. Disperse 5 mg of the catalyst in 1 mL of ethanol solution, and add 20 μL of Nafion membrane solution, then ultrasonicate for 30 min to form a uniform ink. Take out 200 μL and drop it evenly on a 1 cm 2 carbon paper, and use it after drying under an infrared lamp. In an H-type electrolytic cell separated by a Nafion117 proton exchange membrane (PEM) into an anode chamber and a cathode chamber, a platinum sheet is used as the counter electrode, and Ag / AgCl (3.5 M saturated KCl solution) is used as the reference electrode. The hydrophobic carbon paper with a catalyst loading of 1 mg / cm 2 is used as the working electrode. Fill the electrolytic cell with 20 mL of 0.5 M KHCO3 solution. Before testing, bubble 20 mL / min of CO2 into the electrolyte for 30 min until saturated, and then under the condition of continuously introducing CO2, reduce CO2 at a constant potential at the cathode, and calculate the Faraday efficiency of the CO2 reduction products (CO, H2) at different potentials.

[0064] Comparative Example 3 Preparation of N-C-750

[0065] N-C-750 is a highly dispersed nickel-based doped carbon nitride catalytic material prepared by co-pyrolysis treatment of 1,10-phenanthroline (phen) and carbon black at 750 °C.

[0066] Take 100 mg of 1,10-phenanthroline (phen) and 100 mg of carbon black (Vulcan XC-72). Add the above two components to an appropriate amount of absolute ethanol, and after ultrasonic dispersion for 30 min, a uniformly mixed slurry is obtained. After drying the slurry (60 °C, vacuum drying oven) and then grinding, a precursor mixture is prepared.

[0067] The precursor mixture was placed in a quartz boat and then put into a tube furnace. It was heated to 750 °C (heating rate: 5 °C / min) under a nitrogen atmosphere, held for 2 hours, and then naturally cooled to room temperature to obtain a black powder, which is the catalyst Ni-C-750.

[0068] A working electrode was prepared. 5 mg of the catalyst was dispersed in 1 mL of ethanol solution, and 20 μL of Nafion membrane solution was added. After ultrasonic treatment for 30 min, a uniform ink was formed. 200 μL of the ink was taken and evenly dropped onto a 1 cm 2 carbon paper and dried under an infrared lamp for use. In an H-type electrolytic cell separated by a Nafion 117 proton exchange membrane (PEM) into an anodic cell and a cathodic cell, a platinum sheet was used as the counter electrode, and Ag / AgCl (3.5 M saturated KCl solution) was used as the reference electrode. The hydrophobic carbon paper with a catalyst loading of 1 mg / cm 2 was used as the working electrode. 20 mL of 0.5 M KHCO3 solution was loaded into the electrolytic cell. Before the test, CO2 was bubbled into the electrolyte at a rate of 20 mL / min for 30 min until saturation. Then, under the condition of continuously introducing CO2, CO2 was electrochemically reduced at a constant potential at the cathode, and the Faraday efficiencies of the CO2 reduction products (CO, H2) at different potentials were calculated.

[0069] Comparative Example 4 Preparation of Ni(OH)2-N-C-750 Ni(OH)2-N-C-750 is a highly dispersed nickel-based doped carbon nitride catalytic material prepared by co-pyrolysis treatment of nickel hydroxide, 1,10-phenanthroline (phen), and carbon black at 750 °C.

[0070] 6 mg of Ni(OH)2 powder, 100 mg of 1,10-phenanthroline (phen), and 100 mg of carbon black (Vulcan XC-72) were taken. The above three components were added to an appropriate amount of absolute ethanol, and after ultrasonic dispersion for 30 minutes, a uniform mixed slurry was obtained. The slurry was dried (60 °C, in a vacuum drying oven) and then ground to obtain a precursor mixture.

[0071] The precursor mixture was placed in a quartz boat and then put into a tube furnace. It was heated to 750 °C (heating rate: 5 °C / min) under a nitrogen atmosphere, held for 2 hours, and then naturally cooled to room temperature to obtain a black powder, which is the catalyst Ni(OH)2-N-C-750.

[0072] A working electrode was prepared. 5 mg of the catalyst was dispersed in 1 mL of ethanol solution, and 20 μL of Nafion membrane solution was added. After ultrasonic treatment for 30 min, a uniform ink was formed. 200 μL of the ink was taken and evenly dropped onto a 1 cm 2On the carbon paper, it is used after drying under an infrared lamp. In an H-type electrolytic cell separated into an anode chamber and a cathode chamber by a Nafion 117 proton exchange membrane (PEM), a platinum sheet is used as the counter electrode, and Ag / AgCl (3.5 M saturated KCl solution) is used as the reference electrode. The catalyst loading is 1 mg / cm 2 of the hydrophobic carbon paper is used as the working electrode. 20 mL of 0.5 M KHCO3 solution is filled into the electrolytic cell. Before the test, CO2 is bubbled into the electrolyte at 20 mL / min for 30 min until saturated. Then, under the condition of continuously introducing CO2, CO2 is electrochemically reduced at a constant potential at the cathode, and the Faraday efficiencies of the CO2 reduction products (CO, H2) at different potentials are calculated.

[0073] Comparative Example 5 Preparation of Al(OH)3-N-C-750 Al(OH)3-N-C-750 is a carbon-nitrogen catalytic material prepared by co-pyrolysis treatment of aluminum hydroxide, 1,10-phenanthroline (phen), and carbon black at 750 °C.

[0074] Take 6 mg of Al(OH)3 powder, 100 mg of 1,10-phenanthroline (phen), and 100 mg of carbon black (Vulcan XC-72). Add the above three components to an appropriate amount of absolute ethanol, and after ultrasonic dispersion for 30 minutes, a homogeneous mixed slurry is obtained. The slurry is dried (60 °C, vacuum drying oven) and then ground to obtain a precursor mixture.

[0075] Place the precursor mixture in a quartz boat, put it into a tubular furnace, heat it to 750 °C (heating rate 5 °C / min) under a nitrogen atmosphere, keep it warm for 2 hours, and then naturally cool it to room temperature to obtain a black powder, which is the catalyst Al(OH)3-N-C-750, or denoted as Al-N-C-750.

[0076] Prepare the working electrode. Disperse 5 mg of the catalyst in 1 mL of ethanol solution, and add 20 μL of Nafion membrane solution. Ultrasonic for 30 min to form a homogeneous ink. Take out 200 μL and evenly drop it on 1 cm 2 of the carbon paper, and use it after drying under an infrared lamp. In an H-type electrolytic cell separated into an anode chamber and a cathode chamber by a Nafion 117 proton exchange membrane (PEM), a platinum sheet is used as the counter electrode, and Ag / AgCl (3.5 M saturated KCl solution) is used as the reference electrode. The catalyst loading is 1 mg / cm 2The hydrophobic carbon paper serves as the working electrode. 20 mL of 0.5 M KHCO3 solution is filled into the electrolytic cell. Before testing, CO2 is bubbled into the electrolyte at a rate of 20 mL / min for 30 min until saturated. Then, under the condition of continuously introducing CO2, CO2 is reduced at a constant potential at the cathode, and the Faraday efficiency of the CO2 reduction products (CO, H2) at different potentials is calculated.

[0077] In Comparative Example 1, due to the absence of carbon black, carbon black, as a conductive support material, improves the electron transport performance of the catalyst; it has a spherical skeleton structure and can serve as a structural template to control the morphology of the final material (spherical particles); it is structurally stable during pyrolysis, can effectively anchor active sites and avoid sintering. Therefore, the performance of Example 1 is superior to that of Ni-N-750 in Comparative Example 1.

[0078] In Comparative Example 2, due to the absence of 1,10-phenanthroline, 1,10-phenanthroline, as a nitrogen source for material preparation, can generate pyridine N, pyrrole N, graphitic N, etc. under high-temperature pyrolysis; it assists in regulating the electronic structure of the N / C skeleton and improves the selectivity and activity of CO2 reduction. Therefore, the performance of Example 1 is superior to that of Ni-C-750 in Comparative Example 2.

[0079] In Comparative Example 3, due to the absence of NiAl-LDH, NiAl-LDH can provide highly dispersed Ni precursors and be transformed into active Ni sites during pyrolysis; the layered structure is easy to uniformly mix with ligands and carbon sources, which helps in structure control; gas is released during pyrolysis to form a certain degree of pore structure (assisting in pore formation). Therefore, the performance of Example 1 is superior to that of N-C-750 in Comparative Example 3.

[0080] In Comparative Example 4, because Ni(OH)2 is selected, compared with Ni(OH)2, the interlayer water and anions (such as CO3 2- )of NiAl-LDH will decompose and release gas during pyrolysis, contributing to the formation of a porous structure; more importantly, Al 3+ is not reducible and will not participate in the formation of metal particles, which can inhibit the agglomeration and sintering of Ni. Therefore, the performance of Example 1 is superior to that of Ni(OH)2-N-C-750 in Comparative Example 4.

[0081] In Comparative Example 5, because Al(OH)3 is selected and the active metal Ni is lacking, active sites cannot be formed. When heated to >300 °C, Al(OH)3 will dehydrate to form Al2O3 (aluminum oxide), which is an insulating material and does not have electrocatalytic activity, and even hinders electron conduction. Therefore, the performance of Example 1 is superior to that of Al(OH)3-N-C-750 in Comparative Example 5.

[0082] Figure 1 This is the preparation flow chart of the highly dispersed nickel-based carbonitride catalyst of the present invention; FromFigure 1 It can be seen that the preparation method of the present invention is simple and the operation is convenient.

[0083] Figure 2 Scanning electron microscope (SEM) and transmission electron microscope (TEM) images of the highly dispersed nickel-based carbonitride catalyst prepared in Example 1 of the present invention; From Figure 2 It can be seen that the SEM and TEM images together reveal that the material presents a uniform spherical particle structure, and its morphology is dominated by carbon black as a template; at the same time, no obvious metal Ni nanoparticles or agglomeration phenomena are observed, indicating that Ni has been highly dispersed in the carbonitride framework, and the carbon framework exists in an amorphous state, which helps to improve the electron conductivity and the uniformity of the reaction interface.

[0084] Figure 3 X-ray diffraction spectrum (XRD) and X-ray photoelectron spectroscopy (XPS) diagrams of the highly dispersed nickel-based carbonitride catalysts prepared in Examples 1-3 of the present invention, including the high-resolution N 1s diagram showing the N type distribution; From Figure 3 it can be seen that obvious carbon peaks and weak diffraction peaks of the (111) crystal plane of Ni nanoparticles can be observed by XRD, indicating that Ni is highly dispersed in the sample or the size of the nanoparticles is very small; the existence form of N in the highly dispersed nickel-based carbonitride catalysts prepared in Examples 1-3 can be observed as mainly pyridine nitrogen and pyrrole nitrogen by XPS.

[0085] Figure 4 Ni K-edge EXAFS spectrum and Fourier transform spectrum of the highly dispersed nickel-based carbonitride catalyst prepared in Example 1 of the present invention; From Figure 4 it can be seen that Ni in the highly dispersed nickel-based carbonitride catalyst prepared in Example 1 exists in the form of Ni-Ni bonds, and it can be speculated that the existence form of Ni is highly dispersed nano-clusters.

[0086] Figure 5 Faraday efficiency (FE) curves of the CO2 electroreduction reaction of different materials in Examples 1-3 and Comparative Examples 1-5 at different potentials and linear sweep voltammetry (LSV) curves of Examples 1-3; From Figure 5 it can be seen that Ni-N-C-750 shows better CO2RR performance than Ni-N-C-550 and Ni-N-C-950, and the highest FE [[ID=3,4]] COUp to 97.5%, indicating that the catalyst has a significant inhibitory effect on the side reaction HER. It has a highly selective active center structure, that is, an excellent COOH* adsorption and CO desorption equilibrium ability. And Ni-N-C-750 shows a higher current density and a smaller onset potential than Ni-N-C-550 and Ni-N-C-950.

[0087] Figure 6 It is the stability test curve of the highly dispersed nickel-based carbonitride catalyst prepared in Example 1 of the present invention. From Figure 6 it can be seen that in the Flow cell, the catalytic material in Example 1 can electrolyze for 30 h at a current density of -100 mA / cm 2 and the FE remains at about 90%. This proves its good stability and good industrial application potential, showing a good application prospect of the material in future industrial CO2 electroconversion.

[0088] In the highly dispersed nickel-based carbonitride catalyst prepared in the present invention, nickel is highly dispersed, and it has excellent electrocatalytic activity and selectivity. The carbonitride carrier has the functions of a stable structure and electron regulation, which is beneficial to electron transfer and intermediate adsorption.

[0089] The present invention has been described exemplarily above in combination with the embodiments and the drawings. Obviously, the implementation of the present invention is not limited by the above methods. As long as various improvements are made by adopting the method concept and technical solution of the present invention, or the concept and technical solution of the present invention are directly applied to other occasions without improvement, they are all within the protection scope of the present invention.

Claims

1. A preparation method of a highly dispersed nickel-based carbonitride catalyst, characterized in that, It includes the following steps: Step 1: Synthesize the hydrotalcite precursor; Weigh nickel nitrate hexahydrate and aluminum nitrate nonahydrate and dissolve them in deionized water, denoted as solution A, and prepare sodium hydroxide solution B. Use a colloid mill to synthesize the hydrotalcite precursor, namely the NiAl-LDH precursor; Step 2: Prepare the calcination precursor; Disperse the NiAl-LDH precursor, 1,10-phenanthroline, and carbon black in an ethanol solution, disperse evenly, dry in vacuum and then grind and crush to obtain the calcination precursor; Step 3: Prepare the highly dispersed nickel-based carbonitride catalyst; Heat-treat the calcination precursor obtained in Step 2 under a nitrogen atmosphere, and the obtained product is the highly dispersed nickel-based carbonitride catalyst, namely the Ni-N-C catalyst; In Step 1, the molar ratio of nickel nitrate hexahydrate to aluminum nitrate nonahydrate in solution A is 2:1 - 4:1; The total concentration of the nitrate solution A is 0.05 - 1.0 mol / L; The concentration of the sodium hydroxide solution B is 1 mol / L - 4 mol / L; In Step 2, the mass ratio of NiAl-LDH precursor / (1,10-phenanthroline + carbon black) is 0.01 to 0.5; among them, in the mixture of 1,10-phenanthroline and carbon black, the mass percentage of carbon black is 10 - 90%.

2. The preparation method of the highly dispersed nickel-based carbonitride catalyst according to claim 1, wherein: The specific operation of synthesizing the hydrotalcite precursor with a colloid mill is as follows: at a colloid mill rotation speed of 1500 - 9000 rpm, pour solution A and sodium hydroxide solution B simultaneously, and keep at this rotation speed for 1 - 120 min after pouring, take out, wash until neutral, rotary evaporate and dry at 40 - 80 °C, and grind and crush.

3. The preparation method of the highly dispersed nickel-based carbonitride catalyst according to claim 1, wherein: In Step 3, the heat treatment temperature is 550 °C - 950 °C, the heating rate is 0.5 - 10 °C / min, the nitrogen gas flow rate is 20–200 mL / min, and the heat treatment time is 1 - 5 h.

4. A highly dispersed nickel-based carbonitride catalyst, characterized in that: It is prepared according to the preparation method described in any one of claims 1 - 3.

5. The highly dispersed nickel-based carbonitride catalyst according to claim 4, wherein The highly dispersed nickel-based carbonitride catalyst has the following characteristics: (1) Using carbonitride as the carrier, nickel active sites are evenly distributed on the surface; (2) Containing three types of doped nitrogen, namely graphite N, pyridine N, and pyrrole N; (3) The existence form of nickel is Ni-Ni.

6. The highly dispersed nickel-based carbonitride catalyst according to claim 5, wherein: The mass fraction of Ni in the highly dispersed nickel-based carbonitride catalyst is 0.5–5 wt%, and Ni is dispersed in the form of extremely small clusters.

7. The highly dispersed nickel-based carbonitride catalyst according to claim 5, wherein: The total mass fraction of nitrogen element doping in the highly dispersed nickel-based carbonitride catalyst is 1–15 wt%, among which, the proportion of graphite N is 0–40%, the proportion of pyridine N is 20–80%, and the proportion of pyrrole N is 10–40%.

8. Application of the highly dispersed nickel-based carbonitride catalyst described in any one of claims 4 - 7 in the electrocatalytic reaction of selectively reducing CO2 to carbon monoxide.

Citation Information

Patent Citations

  • Nickel monatomic / AlN co-inlaid carbon nanotube electrocatalyst and preparation method thereof

    CN115074750A

  • Catalyst, preparation thereof and application of catalyst in methanation reaction of carbon dioxide

    CN117123205A

  • Method for preparing high-dispersed nickel bases catalyst from hydrotalcite / Nano carbon composite precursor

    CN1958157A